2021
DOI: 10.17583/rimcis.2021.7546
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Families Experiences with Young Children with Intellectual and Developmental Disabilities (IDDs) during COVID-19 Lockdown in Pakistan

Abstract: The shadow impacts of the COVID-19 pandemic are critical, especially for children with intellectual and/or developmental disabilities (IDDs). Financial constraints and home confinement have increased the challenges for caregivers to meet the educational and health needs of children with IDDs. Hence, this research examines the impact of COVID-19 lockdown on families with IDDs children in rural Pakistan. Overall, 176 parents participated in this study and provided valuable responses through interview technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…Una investigación en Paquistán realizada por Mamoom y colaboradores (36) refiere que el beneficio del confinamiento de familias de niños con discapacidades Intelectuales y del desarrollo se restringe a pasar más tiempo con los hijos. Los padres desarrollan muy pocas actividades como jugar, reunirse en familia, hacer ejercicio, comer saludable.…”
Section: Otras áReas De Interésunclassified
“…Una investigación en Paquistán realizada por Mamoom y colaboradores (36) refiere que el beneficio del confinamiento de familias de niños con discapacidades Intelectuales y del desarrollo se restringe a pasar más tiempo con los hijos. Los padres desarrollan muy pocas actividades como jugar, reunirse en familia, hacer ejercicio, comer saludable.…”
Section: Otras áReas De Interésunclassified
“…Author and Year Findings 1. (Munir et al, 2021) Financial constraints, social isolation, deteriorated health conditions of their children, reduced or no health services, closure of educational institutes, negative behavioural impacts, and slow mental development are all challenges faced by parents of children with intellectual and developmental disabilities. Staying at home, on the other hand, results in improved relationships, according to respondents.…”
Section: Reviewed Articles and Summary Of The Findingsmentioning
confidence: 99%
“…Some studies point out challenges that have been faced by schoolchildren and families. For example, Munir et al (2021) highlight that schoolchildren and families faced financial, psychological, and physical challenges, but on the positive side the relationships between family members often improved due to staying at home. Similarly, Mian and Chachar (2020) identify a variety of issues that were encountered by both children and parents due to restrictions that were imposed.…”
Section: Challenges Facedmentioning
confidence: 99%
“…Four studies documented limited or unequal access to information on available services, assistance, and programmes offered by either NGOs or governmental agencies. Research in rural Pakistan found that families with disabled children had no channel to receive information on services available to them (Munir et al, 2021;Naz et al, 2010). Moreover, a study on the perspectives of disabled children and their mothers in rural Vietnam discovered that the application process for disability support services was not transparent and could only be accessed by families selected by the People's Committee (Ngo et al, 2013).…”
Section: Limited or Unequal Access To Information On Available Resourcesmentioning
confidence: 99%
“…The most frequently mentioned need at the family level (10 out of 23 studies) was psychosocial support for caregivers, such as socioemotional support programmes for families (Richard, 2014), professional psychological counselling services (Maridal et al, 2021;Munir et al, 2021), direct training programmes on parental skills to better aid child development (Naz et al, 2010), peer support programmes for caregivers to share their experiences in a safe space (Ngo et al, 2013;Shang et al, 2011), and other forms of specific social support for mothers (Shang & Fisher, 2014). The second most identified (eight out of 23) need was financial support for families, such as implementing targeted poverty alleviation programmes (Kiling et al, 2019;Ngo et al, 2013) and providing economic resources for girls with disabilities specifically (Don et al, 2015).…”
Section: Family-level Needsmentioning
confidence: 99%